Mothers Adherence to Global Infant and Young Child Feeding Strategies in Ketu North District, Volta Region - Ghana - Appiah, Prince Kubi; Dzata, Wilson Mensah; Bonchel, Duut Abdulai; Korklu, Anang Rhoda Naa; Ayeley, Doe Jessica Naa; Fenu, Georgina Agartha; Abdul-Rahman, Timay Ibrahim (European Scientific Journal, ESJ, 2017)
Background: Infant and young child nutrition has been engaging the attention of scientists and governments over the years. Their feeding practices comprise both breastfeeding as well as complementary feeding which have major role in determining the nutritional status of the child, therefore, there has been a well-established link between malnutrition and infant feeding. Children are the future of the world and yet the most vulnerable population, with some 6.6 million children dying before their fifth birthday globally. Studies have shown that poor breastfeeding and complementary feeding practices, coupled with high rates of morbidity from infectious diseases are the primary causes of malnutrition and death in the first two years of life. Ketu-North district noted that even though nutrition and health programmes were in place, breastfeeding coverage has been between 53% in 2013 and 69% in 2015. This study sought to assess mothers or caregivers adherence to Infant and Young Child Feeding (IYCF) practices in Ketu North District of the Volta Region in Ghana. Method: A crosssectional study among mothers/caregivers with children 0-24 months in the district. Multistage sampling techniques was used to select 518 respondents. A semi-structured questionnaire was used to conduct face-to-face interviews. Statistical software Epi Data version 3.1 and Stata version 12.1 were used for data entry and analysis respectively. Descriptive statistics was presented in tables and graphs. Beyond descriptive statistics, associations between the outcome and predictor variables were analysed using Pearson chi-square and logistics regression. P-value < .05 was considered as statistically significant. Findings: Respondents had a mean age of 25.6 years (±3.6 SD). Only 8.7% of the mothers adhered to IYCF strategies with practices of exclusive breastfeeding, complementary feeding, hygiene and sanitation practices, meal variety, and meal frequency being 57.9%, 38.0%, 16.2%, 37.1%, and 33.2% respectively. Ethnicity (p < .000), age of child (p = .032), employment (p =.041) and level of education (p = .042) were found to be associated with adherence to IYCF strategies. Conclusions: Adherence to infant and young child feeding practices were not encouraging in the district therefore the district health management team need to strengthen health education and implement other behaviour change interventions to improve on the adherence to feeding strategies. Further studies should be conducted to assess factors influencing the low adherence to the feeding strategies in the district.